2021
DOI: 10.1186/s13620-021-00204-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different attitudes towards paratuberculosis control using cluster analysis applied on data from an anonymous survey among German cattle farmers

Abstract: Background Paratuberculosis is a common disease in ruminants, causing economic losses in livestock farming, and a relationship between the exposure to its causative agent Mycobacterium avium subsp. paratuberculosis, and Crohn’s disease in humans is discussed. Despite this, only a minority of cattle farmers have enroled in voluntary control programmes in most countries. Therefore, this study aimed at investigating the farmer’s opinion on paratuberculosis and their motivations to participate in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Despite the fact that the costs of the program for participating farmers were limited (half of the testing costs and some additional efforts to improve hygiene) and were low compared to the benefits, the majority of Thuringian cattle farmers have yet to register in the program. This reticence was consistent with our findings in a previous study regarding attitudes towards paratuberculosis control using cluster analysis applied on data from an anonymous survey among cattle farmers in Thuringia and Saxony [ 39 ]. In this study, we identified four groups of farmers tagged ‘free supporters’, ‘affected supporters’, ‘sceptics’, and ‘deniers’.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the fact that the costs of the program for participating farmers were limited (half of the testing costs and some additional efforts to improve hygiene) and were low compared to the benefits, the majority of Thuringian cattle farmers have yet to register in the program. This reticence was consistent with our findings in a previous study regarding attitudes towards paratuberculosis control using cluster analysis applied on data from an anonymous survey among cattle farmers in Thuringia and Saxony [ 39 ]. In this study, we identified four groups of farmers tagged ‘free supporters’, ‘affected supporters’, ‘sceptics’, and ‘deniers’.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the supporters of the program, the two groups of farmers tagged as ‘sceptics’ and ‘deniers’ did not consider paratuberculosis a dangerous epizootic disease, and the ‘deniers’ would not enroll in a voluntary control program even if the pathogen would have been found in their herd. These farmers mentioned the costs and the inaccuracy of diagnostic tests as obstacles that hamper their enrollment [ 39 ]. The reluctance of farmers to adopt JD control measures was often justified with the argument that existing tests fall short of offering a reliable basis for consistent control and that the available tests still do not offer the necessary sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the farmer and the herdsman were highly motivated to struggle through the tribulations of paratuberculosis control, which is specific but not uncommon among Thuringian dairy farmers. A former study investigating the attitudes of farmers toward paratuberculosis control in that region identified a high proportion of cattle farmers supporting the activities of paratuberculosis control [ 56 ]. For those who are interested in paratuberculosis control but still undecisive, this report may be a good example showing that the disease can be controlled and even that the elimination of the infectious agent might be an achievable goal.…”
Section: Discussionmentioning
confidence: 99%
“…The farms that buy and sell dairy cattle also have the highest infection risk for MAP infection [37]. Furthermore, the attitudes of farmers towards MAP and their beliefs are very important for the control of MAP [38]. In China, farmers in small farms usually have a relatively low knowledge and a negative attitude towards the control of animal diseases, and most of them buy dairy cattle from others.…”
Section: Discussionmentioning
confidence: 99%